Assessment of the Recession Phase in a Drip Irrigated Blueberry (Hybrid Cross of Vaccinium sp.) Crop under Different Irrigation Design Criteria and Irrigation Scheduling in Concordia, Entre Ríos, Argentina - A. Pannunzio; E. A. Holzapfel; P. Texeira (Current Topics in Agricultural Sciences Vol. 6, 2022)
The increase of human population generates the need to improve the efficiency of food production. A thorough planning is required following the scope of economic and sustainable development, being irrigation a basic tool, however water availability is restricted, and it obliges farmers to progress increasing water productivity. Irrigation uses around 70% of total available fresh water and the water application efficiency is around 40%. Irrigation systems must follow strong criteria at the design stage to achieve high values of water productivity. Maintenance is indispensable to follow the original functioning level of those systems. At last, the daily precise management of systems, following soil water potential, considering the effective rain storage at root depth of the crop and the evolution of daily evapotranspiration, preserving natural resources, are relevant to achieve low values of water footprint of this crop. The aim of this work is to give tools to decide how to design and irrigate efficiently considering recession phase in drip irrigation. In an 8-year drip irrigation system, the Uniformity Coefficient of Christiansen (UCC) measured was 95,14 %, the Uniform Coefficient of the Minor Quart (UCMQ) was 93,16 %. The Total Distribution Efficiency (EDT) was 95,13 % when measurements finished while the irrigation systems is switch of. When measurements also considered the volume collected during the “recession phase in drip irrigation” and the “volume of water collected during recession phase” collected at different points, EDT was 95,13 %. Moreover, when three different typical soil of the area were considered, the EDT was, 91,85 %, 9,47 % and 90,30 % respectively, according with different water storage capacity of each soil. The Total Distribution Efficient is a strong method, to evaluate the design and management of drip irrigation systems, under different design criteria, management practices and maintenance of the systems. Water footprint was measure and values obtain were 846, 310, 223, 212, 172 and 218 liters per kg of fresh fruit in the period 2010-2015.